EFFECT OF SYSTEMATIC SAMPLING INTENSITY IN THE HYPSOMETRIC RELATIONSHIP OF TEAK STANDS - PELISSARI, Allan Libanio; DAVID, Hassan Camil; PÉLLICO NETTO, Sylvio; CALDEIRA, Sidney Fernando; FIGUEIREDO FILHO, Afonso; MARINHESKI FILHO, Ataídes (Brazilian Journal of Biometrics, 2016)
Traditionally, in teak stands, systematic sampling is applied to select trees in plots, where their heights are measured to fit hypsometric models, aiming to facilitate its implementation in forest inventories. Therefore, assuming the hypothesis that the hypsometric relationship is affected by selection of trees, the aim of this work was to evaluate the effect of systematic sampling intensities in the hypsometric modeling to estimate the total height, dominant height and total volume in a forest inventory of teak stands. Dendrometric data were collected and hypsometric models were fitted to different systematic sampling intensities: 10%, 20%, 30%, 40% and 50% of the first border trees per plot. Also, 100% of the trees were considered as a control treatment and arranged in a randomized block design. The Dunnett test was used to detect statistical differences between treatment means. It is suggested to measure 40% of tree heights in a plot to obtain statistically appropriate fits of hypsometric models in young teak stands. However, through low systematic sampling intensities of trees in plots, it is possible to obtain average values of dominant heights statistically equal to those of all measured trees.